Britain and Africa in the twenty-first century between ambition and pragmatism - Beswick, Danielle; Fisher, Jonathan 1985-; Hurt, Stephen R. (Manchester University Press, 2021)
Britain and Africa in the twenty-first century provides the first analysis of UK-Africa policy in the era of austerity, Conservative government and Brexit. It explores how Britain's relationship with Africa has evolved since the days of Blair, Brown and "Make Poverty History" and examines how a changing UK political environment, and international context, has impacted upon this longstanding - and deeply complex - relationship. This edited collection includes contributions from leading UK- and Africa-based scholars, as well as from Chatham House's Africa Programme Head and the Chair of the All Party Parliamentary Group on Africa. Examining trade, security, aid and peacekeeping, as well as the role of political parties, advocacy groups and the UK population itself, Britain and Africa provides an indispensable reference point for researchers and practitioners interested in contemporary UK-Africa relations and the place of Africa in British foreign policy
Literaturangaben
Keywords: Außenpolitik; Afrika; Großbritannien; Aufsatzsammlung